STRATEGIC ALLIANCES AND PARTNERSHIPS - S. Vasilenko (Вестник университета, 2016)
Strategic alliances are an integral alternative to run a new zero-based business or inorganic way of mergers and acquisitions. Explaining the importance of alliances and partnerships, the article investigates the sixth power question of industry competitiveness, which can be an addition to the Porter's five force model. Under the globalization process and the latest achievements in the sphere of high technologies, many companies are forced to focus on the benefits of alliances and partnerships with complementors. The author believes that the complementors have no need to increase or decrease the competitiveness of firms in various industries. They just add one more layer of the structural complexity to the competitive environment.